2010
DOI: 10.1242/jcs.057968
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of retinoic acid and FGF9 onNanos2expression and meiotic entry of mouse germ cells

Abstract: SummaryIn the mouse, three genes that are homologous to the Drosophila Nanos (Nos) gene have been identified. Deletion of one of these genes, Nanos2, results in male sterility, owing to loss of germ cells during fetal life. Before apoptosis, Nanos2-null gonocytes enter meiosis, suggesting that Nanos2 functions as a meiotic repressor. Here, we show that Nanos2 is continuously expressed in male germ cells from fetal gonocytes to postnatal spermatogonial stem cells. We observed that the promeiotic factor AtRA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 53 publications
(56 reference statements)
7
128
0
Order By: Relevance
“…53 We found that several transcripts were differentially regulated in a manner consistent with NOTCH signaling activation in Sertoli cells and with premature differentiation of germ cells. For instance, RBPJ target genes such as Hey1 and Heyl were upregulated in Sertoli cells, as expected; in germ cells, Nanos2, a gene that suppresses meiosis, 54 was downregulated, and genes that are expressed at the beginning of or during meiosis, such as Stra8 and Rec8, 55,56 were all upregulated (GSE37073). Furthermore, in accord with the observation that germ cell differentiation had taken place, a significant decrease in Pou5f1 (a marker for undifferentiated spermatogonia) 57 and a significant increase in Sohlh2 (a marker for differentiating spermatogonia) 58 were also found in these mutant germ cells.…”
Section: Amh-nicd1 Mouse Modelsupporting
confidence: 68%
“…53 We found that several transcripts were differentially regulated in a manner consistent with NOTCH signaling activation in Sertoli cells and with premature differentiation of germ cells. For instance, RBPJ target genes such as Hey1 and Heyl were upregulated in Sertoli cells, as expected; in germ cells, Nanos2, a gene that suppresses meiosis, 54 was downregulated, and genes that are expressed at the beginning of or during meiosis, such as Stra8 and Rec8, 55,56 were all upregulated (GSE37073). Furthermore, in accord with the observation that germ cell differentiation had taken place, a significant decrease in Pou5f1 (a marker for undifferentiated spermatogonia) 57 and a significant increase in Sohlh2 (a marker for differentiating spermatogonia) 58 were also found in these mutant germ cells.…”
Section: Amh-nicd1 Mouse Modelsupporting
confidence: 68%
“…By contrast, the addition of RA reduced NANOS2 expression and concomitantly induced KIT and STRA8 expression in these cells (Barrios et al 2010). Moreover, in PND7 mice, PLZF, a transcription factor required for SSC maintenance (Buaas et al 2004), was shown to act as a repressor on the Kit promoter, preventing KIT expression, whereas isolated Thy1 C spermatogonia from Plzf K/K mice showed more than a doubling in their KIT expression (Filipponi et al 2007).…”
Section: Spermatogonia and Ssc Differentiationmentioning
confidence: 94%
“…C , KIT -mouse germ cells express high levels of NANOS2, a RNA-binding protein involved in SSC self-renewal and in the suppression of spermatogonial differentiation (Suzuki & Saga 2008, Suzuki et al 2009, Sada et al 2012, in response to FGF9, a growth factor produced by Sertoli cells (Barrios et al 2010). By contrast, the addition of RA reduced NANOS2 expression and concomitantly induced KIT and STRA8 expression in these cells (Barrios et al 2010).…”
Section: Spermatogonia and Ssc Differentiationmentioning
confidence: 99%
“…This action prevents meiosis from occurring in the fetal testis, and assists in the commitment of male germ cells to the spermatogenic pathway. Other factors involved in this commitment of germ cells to the male program include FGF9 and NANOS2 (Barrios et al, 2010, Bowles et al, 2010, Suzuki and Saga, 2008. Beginning at E11.5, male germ cells rely upon FGF9 for survival, and it has been proposed that FGF9 supports NANOS2 production in these cells to prevent meiotic entry and the activation of events downstream of RA (Barrios et al, 2010, Bowles et al, 2010, DiNapoli et al, 2006, Suzuki and Saga, 2008.…”
Section: From the Site Of Origin To The Gonadal Ridgementioning
confidence: 99%